Taxation of Special Transactions - Najib, Ahmad; Pakpahan, Kristina Evana; Pahala, Indra; Wahono, Puji (The Future of Education Journal, 2025)
This study comprehensively examines the application of taxation in special transactions in Indonesia, including Build-Operate-Transfer (BOT) cooperation models, finance leases with purchase options, joint operations, and foundations. The research is motivated by the complexity of regulations and the challenges in applying tax rules to special transactions commonly used by business entities and nonprofit organizations in Indonesia. This study employs a descriptive qualitative method with a literature study approach, reviewing laws and regulations, academic literature, and previous research findings to gain a deep understanding of the normative aspects and practical implementation of taxation in the field. The findings indicate that the taxation of BOT schemes has gained legal certainty through Government Regulation No. 34/2017, which classifies all income as rental income subject to a final tax of 10% based on market value or the highest NJOP (government-assessed property value). For finance leases with purchase options, tax regulations specifically address income tax and VAT treatment; however, challenges remain in practice, particularly in asset depreciation and expense recognition, especially in cases of bankruptcy or changes in the lease term. Joint operations face the risk of double taxation due to the lack of specific regulations governing intra-KSO (joint operation) transactions, leading to potential tax redundancy and inefficiencies in tax administration. Meanwhile, foundations engaged in the education sector have fulfilled their administrative tax obligations; however, the utilization of available tax facilities remains suboptimal, resulting in less-than-optimal income tax efficiency. These findings highlight the need for regulatory harmonization, enhanced outreach, and capacity building for business actors and organizations to better understand and utilize tax provisions for special transactions. This research is expected to serve as a useful reference for stakeholders in supporting relevant policy analysis and formulation aimed at improving tax effectiveness and compliance in Indonesia.